2006
DOI: 10.1177/08830738060210011501
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Phenotype of South African Children With Neurofibromatosis 1

Abstract: Forty-eight children with neurofibromatosis 1 presenting between 2000 and 2004 were reviewed for their clinical phenotype, and data were compared with published reports. The median age at presentation was 4 years (range 10 days to 12 years). The male to female ratio was similar (22 male:26 female). There were frequencies of café au lait spots, axillary freckling, Lisch nodules, and new mutations comparable to those cited in the literature. Fewer patients had neurofibromas (4%), but more patients had plexiform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…The diagnosis is made according to the NIH 1988 clinical diagnostic criteria 8 . Clinical features of NF-1 detected in our patients were similar with many studies reported in literature previously 13,14 .…”
Section: Discussionsupporting
confidence: 91%
“…The diagnosis is made according to the NIH 1988 clinical diagnostic criteria 8 . Clinical features of NF-1 detected in our patients were similar with many studies reported in literature previously 13,14 .…”
Section: Discussionsupporting
confidence: 91%
“…However, in a third series, these lesions were not associated with intellectual impairment 9 . In a study by Ramanjam et al, the rate of learning difficulty was found to be 70% in African children with NF1 and this ratio, which is higher than others in the literature, was tried to be explained by reasons such as poor socioeconomic level, bad nutrition, maternal education and education system 21 . In our study, 22 (61.1%) of the patients with T2H of cerebral MRI were girls and this relationship was statistically significant.…”
Section: Discussionmentioning
confidence: 92%
“…Blazo et al reported that optic glioma was found in 15% of 84 patients with NF 1 [27]. Ramanjam et al reported that 6% of patients with NF 1 had optic glioma in in their study [10]. In the study of Ferner et al, the optic glioma rate was reported as 15% [28].…”
Section: Discussionmentioning
confidence: 92%
“…In NF1 disease, the sexes are generally affected equally [14]. In the study of Ramanjam et al, 26 of 48 patients diagnosed with NF1 were reported as female (54%) and 22 as male (46%) [10]. In the study of Corsello et al, it was reported that 49.1% of the patients were girls and 50.9% were boys [15].…”
Section: Discussionmentioning
confidence: 99%